Предмет: Математика,
автор: соонышко1
выполните делениеномер 1198
Приложения:
![](https://files.topotvet.com/i/2d2/2d2da5a0d3841b328e723e9abb97b4bd.jpg)
Ответы
Автор ответа:
0
1)
![frac{5x-3}{2}: frac{3-5x}{7}= frac{5x-3}{2} * frac{7}{3-5x}= frac{(5x-3)*7}{2(3-5x)}= frac{(5x-3)*7}{2(-(-3+5x))}=- frac{(5x-3)*7}{2(-3+5x)}= frac{5x-3}{2}: frac{3-5x}{7}= frac{5x-3}{2} * frac{7}{3-5x}= frac{(5x-3)*7}{2(3-5x)}= frac{(5x-3)*7}{2(-(-3+5x))}=- frac{(5x-3)*7}{2(-3+5x)}=](https://tex.z-dn.net/?f=+frac%7B5x-3%7D%7B2%7D%3A+frac%7B3-5x%7D%7B7%7D%3D+frac%7B5x-3%7D%7B2%7D+%2A+frac%7B7%7D%7B3-5x%7D%3D+frac%7B%285x-3%29%2A7%7D%7B2%283-5x%29%7D%3D+frac%7B%285x-3%29%2A7%7D%7B2%28-%28-3%2B5x%29%29%7D%3D-+frac%7B%285x-3%29%2A7%7D%7B2%28-3%2B5x%29%7D%3D+++)
![= -frac{(5x-3)*7}{2(5x-3)}=- frac{7}{2}=-3 frac{1}{2} = -frac{(5x-3)*7}{2(5x-3)}=- frac{7}{2}=-3 frac{1}{2}](https://tex.z-dn.net/?f=%3D+-frac%7B%285x-3%29%2A7%7D%7B2%285x-3%29%7D%3D-+frac%7B7%7D%7B2%7D%3D-3+frac%7B1%7D%7B2%7D+++)
2)
Сразу перевернул...
![frac{9y-2}{5}* frac{3}{2-9y}= frac{(9y-2)*3}{5(2-9y)}=- frac{(9y-2)*3}{5(9y-2)}=- frac{3}{5} frac{9y-2}{5}* frac{3}{2-9y}= frac{(9y-2)*3}{5(2-9y)}=- frac{(9y-2)*3}{5(9y-2)}=- frac{3}{5}](https://tex.z-dn.net/?f=+frac%7B9y-2%7D%7B5%7D%2A+frac%7B3%7D%7B2-9y%7D%3D+frac%7B%289y-2%29%2A3%7D%7B5%282-9y%29%7D%3D-+frac%7B%289y-2%29%2A3%7D%7B5%289y-2%29%7D%3D-+frac%7B3%7D%7B5%7D+++++)
3)
![frac{7-x}{6} * frac{9}{x-7}= frac{7-x}{2} * frac{3}{x-7}= frac{(7-x)*3}{2(x-7)}= -frac{(x-7)*3}{2(x-7)}=- frac{3}{2}=-1 frac{1}{2} frac{7-x}{6} * frac{9}{x-7}= frac{7-x}{2} * frac{3}{x-7}= frac{(7-x)*3}{2(x-7)}= -frac{(x-7)*3}{2(x-7)}=- frac{3}{2}=-1 frac{1}{2}](https://tex.z-dn.net/?f=+frac%7B7-x%7D%7B6%7D+%2A+frac%7B9%7D%7Bx-7%7D%3D+frac%7B7-x%7D%7B2%7D+%2A+frac%7B3%7D%7Bx-7%7D%3D+frac%7B%287-x%29%2A3%7D%7B2%28x-7%29%7D%3D+-frac%7B%28x-7%29%2A3%7D%7B2%28x-7%29%7D%3D-+frac%7B3%7D%7B2%7D%3D-1+frac%7B1%7D%7B2%7D+)
4)
![frac{12-ab}{5} * frac{6}{ab-12}= frac{(12-ab)*6}{5(ab-12)}=- frac{(ab-12)*6}{5(ab-12)}=- frac{6}{5}=-1 frac{1}{5} frac{12-ab}{5} * frac{6}{ab-12}= frac{(12-ab)*6}{5(ab-12)}=- frac{(ab-12)*6}{5(ab-12)}=- frac{6}{5}=-1 frac{1}{5}](https://tex.z-dn.net/?f=+frac%7B12-ab%7D%7B5%7D+%2A+frac%7B6%7D%7Bab-12%7D%3D+frac%7B%2812-ab%29%2A6%7D%7B5%28ab-12%29%7D%3D-+frac%7B%28ab-12%29%2A6%7D%7B5%28ab-12%29%7D%3D-+frac%7B6%7D%7B5%7D%3D-1+frac%7B1%7D%7B5%7D++++)
2)
Сразу перевернул...
3)
4)
Похожие вопросы
Предмет: Физкультура и спорт,
автор: zzipp2005
Предмет: Литература,
автор: krumu4
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: montikov2004
Предмет: Информатика,
автор: пнппр